Financial contagion patterns in individual economic sectors. the day-of-the-week effect from the Polish, Russian and Romanian markets - Elena Valentina Țilică (Journal of Risk and Financial Management, 2021)
This paper studies the presence of the day-of-the-week (DOW) effect in the financial contagion process observed on individual economic sectors from the Post-Communist East European markets. The only markets that provide national-specific sector indices determined throughout the 2008 financial crisis are Poland, Romania and Russia. The novel methodology combines two existing perspectives from financial literature, by employing a GJR-GARCH framework on a dummy regression model that accounts for both the crisis period and the weekdays. All indices show the presence of the DOW effect during the crisis and/or non-crisis periods, thus signaling their low level of market efficiency. However, the contagion process affects only eight of these indices: the banking, IT and oil and gas sectors from Poland, the chemical, telecommunication and transport sectors from Russia and energy sectors from Russia and Romania. All of them show signs of the DOW effect in contagion: five exhibit higher spillovers on crisis Mondays, while the other three show other weekday patterns. The findings suggest that the DOW effect is not specific to certain countries or certain economic sectors.
Keywords: 330; day-of-the-week effect; emerging stock markets; financial contagion; financial sectors; real economy sectors